Risanto’s Formulas is more Accurate in Determining Estimated Fetal Weight Based on Maternal Fundal Height - Titisar, Hanifah I; Siswosudarmo, Risanto (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: To compare the accuracy of Johnson’s and Risanto’s formulas in determining estimated fetal weight based on maternal fundal height (FH). Methods: This was a cross sectional study, consisting of 655 pregnant women from Dr. Sardjito Hospital and affiliated hospital sat 37-42 weeks of gestation. Fundal height was measured from the symphisis to the top of uterine fundus, using inverted unelastic flexible tape. EFW based on Johnson’s and Risanto’s formulas were compared with the actualbirth weight. Wilcox on analysis was used for statistical analysis. Results: Mean EFW of Johnson’s formula was 3136 ± 392.2 grams and EFW of Risanto’s formula was 3056 ± 322.5 grams and mean actual birth weight was 3021 ± 341.1 grams. The mean difference between EFW of Johnson’s formula and the actual birth weight was 156.1 ± 107.3 grams, and mean difference between EFW of Risanto’s formula and the actual birth weight was 100.8 ± 86.1 grams. Those two differences was statistically significant (p=0.001). Conclusion: This study showed that Risanto’s formula was more accurate than Johnson’s in predicting birth weight based on the maternal’s fundal height. [Indones J Obstet Gynecol 2013; 1-3: 149-51] Keywords: actual birth weight, fundal height, Johnson’s formula, Risanto’s formula